ENHANCING STUDENT ENGAGEMENT THROUGH OPTIMAL CLASS PROVISION: THE POTENTIAL OF THE SIMPLEX METHOD IN MOVING CLASS SYSTEMS - Fadia, Virotun Nisaul; Susanti, Dina Anggraini; Aminah, Sukma Ayu Nur; Nafi'ah, Imroatun; Munawwir, Zainul (STKIP PGRI Situbondo, 2024)
Implementing Moving Class at SMAN 1 Panji aims to make students focus on studying subjects of interest that will be used for college entrance tests. The number of students who do not get classes in the subjects of interest because the provision of courses in the implementation of Moving Class has not been optimal causes many students not to be enthusiastic about learning. By considering these problems, it is necessary to have a literature review on the simplex method to know whether or not the simplex method can be used as a method in optimizing the provision of classes in the implementation of Moving Class so that all students get courses according to their interests and students will be more enthusiastic in participating in learning. A literature review is used to determine whether or not the simplex method can be used to assess the provision of classes in implementing Moving Class. In previous studies, the simplex method was widely used to optimize production, profits, and also a combination of production because it has several constraints and linear limits, so it was concluded that the simplex method could be used to optimize the provision of classes on the implementation of Moving Class because it also has linear constraints.